Islandness, tourism and urbanization in the Balearic Islands - Pons Esteva, Antoni (Documents d'Anàlisi Geogràfica, 2019)
Islandness, a function linked to the insular experience, and tourism are two key factors that have conditioned the urbanization process in the Balearic Islands. Islandness, understood as a disconnection from the mainland and in terms of the small size of the islands, has conditioned the lower degree of urbanization of the Balearic coast in comparison to the nearby continental Mediterranean regions. Furthermore, larger islands, such as Mallorca, and those that are better communicated with the exterior, such as Mallorca or Ibiza, have also experienced higher degrees of urbanization than smaller ones, like Formentera, or worse connected ones, like Menorca or Formentera. On the other hand, the island condition has been an attraction factor for the tourism industry. Generally, islands are important tourist destinations and the Balearic Islands are one of the main tourist spots of the Mediterranean. Tourism requires spaces of production and the urbanization of the coastline reflects the degree of tourism pressure.